2014
DOI: 10.4103/0972-0707.131787
|View full text |Cite
|
Sign up to set email alerts
|

The effect of casein phosphopeptide-amorphous calcium phosphate paste and sodium fluoride mouthwash on the prevention of dentine erosion: An in vitro study

Abstract: Aim:The purpose was to compare the effect of 0.2% sodium fluoride mouthwash and casein phosphopeptide-amorphous calcium phosphate paste on prevention of dentin erosion.Materials and Methods:Buccal surfaces of 36 sound premolar teeth were ground flat and polished with abrasive discs. Half the polished surfaces were covered with tape to maintain a reference surface. Samples were randomly allocated into three groups. Group A was pretreated with tooth mousse (TM) 4 times a day for 5 days. Group B was pretreated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
5
1
2
Order By: Relevance
“…This may explain the absence of significant difference specimens treated with fluoride varnish (without laser). Other study has found that fluoride (0.2% sodium fluoride mouthwash) was able to control dental erosion, however different to the present study fluoride was applied 4 times a day (1 min each time) during 5 days and samples was placed in a glass of Coca-Cola 4 times a day (2 min each time) during 3 days (19).…”
Section: Discussioncontrasting
confidence: 65%
“…This may explain the absence of significant difference specimens treated with fluoride varnish (without laser). Other study has found that fluoride (0.2% sodium fluoride mouthwash) was able to control dental erosion, however different to the present study fluoride was applied 4 times a day (1 min each time) during 5 days and samples was placed in a glass of Coca-Cola 4 times a day (2 min each time) during 3 days (19).…”
Section: Discussioncontrasting
confidence: 65%
“…Vários estudos avaliaram o poder preventivo das pastas de CPP-ACP aplicadas no esmalte previamente ao desafio erosivo, associadas ou não ao fluoreto, comparadas a diversos outros agentes protetores, utilizando protocolos de estudo distintos e enquanto alguns 3,5,40 obtiveram resultados positivos, outros 25,27,42,44,[47][48][49][50] encontraram resultados pouco favoráveis.…”
Section: Resultados O Erosãounclassified
“…It maintains optimal concentrations of ions on tooth surfaces to enhance remineralization. In vitro studies have reported that CPP-ACP can be absorbed by the salivary pellicle and dental plaque (17). The CPP has an important role as an ACP carrier localizing the highly soluble calcium phosphate phase at the tooth surface; thereby, induced remineralization (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%